Change in Gross Motor Abilities of Girls and Women with Rett Syndrome Over a 3- to 4- Year Period - Foley, K.; Downs, Jennepher; Bebbington, A.; Jacoby, P.; Girdler, S.; Kaufmann, W.; Leonard, H. (Sage, 2011)
Rett syndrome is a rare but severe neurological disorder typically associated with a mutation in the MECP2 gene. We describe change in gross motor function over 3 to 4 years for 70 subjects participating in the Australian Rett Syndrome Database. Linear regression was used to assess relationships with age, genotype, and general and complex gross motor skills scores measured on the Gross Motor Scale for Rett syndrome. Skills were slightly better or maintained in approximately 40% of subjects and slightly decreased in approximately 60%. Teenagers and women who walked in 2004 were less likely to lose complex skills than those younger. Girls with a p.R294X mutation were more likely to lose complex motor skills, otherwise skill changes were spread across the mutation categories. In conclusion, small changes were observed over this period with greater stability of skills in teenagers and women with the ability to walk.